Novel selective glucocorticoid receptor modulator GRM-01 demonstrates dissociation of anti-inflammatory effects from adverse effects on glucose and bone metabolism - Jakob, Florian; Hennen, Stephanie; Gautrois, Michael; Khalil, Feras; Lockhart, Andrew (Frontiers in Pharmacology, 2025)
IntroductionThe development of selective GR agonist and modulators (SEGRAMs) aimed to minimize the adverse effects of chronic glucocorticoid treatment (e.g., hyperglycemia and osteoporosis) by separating the transactivation and transrepression activities of the glucocorticoid receptor (GR). Herein we report the pharmacologic profile of clinical candidate GRM-01, a novel, orally available, non-steroidal SEGRAM.MethodsIn vitro GR, progesterone receptor (PR), and mineralocorticoid receptor (MR) binding and reporter gene assays were conducted to determine GRM-01 potency and selectivity. Anti-inflammatory effects were investigated in vitro using functional assays in rat and human whole blood, human lung cells, and primary fibroblast-like synoviocytes from human donors with rheumatoid arthritis. In vitro assays measured tyrosine aminotransferase [TAT] activity in human hepatocytes and osteoprotegerin release from human osteoblasts as markers of glucose and bone metabolism, respectively. In vivo studies examined the effect of GRM-01 on biomarkers in a rat model of inflammation and on cortisol levels in Cynomolgus monkeys. Animal pharmacokinetics (PK) for GRM-01 were determined and used to predict its human PK.ResultsGRM-01 is a potent and selective ligand of human GR versus human PR and MR (inhibition constant = 12 vs. 3,700 and >10,000 nM, respectively). GRM-01 displayed partial induction (transactivation) at the GR (half-maximal effective concentration [EC50] = 60.2 nM, efficacy 31.8%) versus prednisolone (EC50 = 24.3 nM, efficacy 80.5%). GRM-01 demonstrated anti-inflammatory efficacy, inhibiting tumor necrosis factor-α and interferon-γ release in whole blood assays, and interleukin-6 release in cellular assays. GRM-01 weakly increased TAT activity in HepG2 cells (efficacy 14.0% vs. 92.4% with prednisolone) and partially inhibited osteoprotegerin release in MG-63 cells (by 58% vs. 100%). In vivo, GRM-01 dose-dependently reduced rat ankle swelling, had anti-nociceptive effects, and did not increase blood glucose. In Cynomolgus monkeys, GRM-01 dose-dependently reduced plasma cortisol. Animal PK found that GRM-01 had high oral bioavailability, generally low clearance, and good tissue partitioning. The predicted human total plasma clearance of GRM-01 was 0.25 mL/min/kg, volume of distribution 2.124 L/kg, and half-life ∼98 h.ConclusionGRM-01 displays a favorable preclinical pharmacologic profile consistent with a SEGRAM, and based on this is currently in Phase 1 development.